The bones of ruin - Raughley, Sarah (New York : Margaret K. McElderry Books, 2021)
"An African tightrope walker who cannot die gets involved with a mysterious society that's convinced the world is ending and is drafted into the fight-to-the-death Tournament of Freaks, where she learns the terrible truth of who and what she really is"--Provided by publisher.
Kirkus Review
Publishers Weekly Annex
Kirkus Review, July 2021
Publishers Weekly Annex, September 2021
5-8.
English.
Keywords: Ability -- Juvenile fiction; Black people -- England -- Juvenile fiction; Contests -- Juvenile fiction; End of the world -- Juvenile fiction; Ability -- Fiction; Black people -- England -- Fiction; Contests -- Fiction; End of the world -- Fiction; Supernatural -- Fiction; Ability -- Fiction; Black people -- England -- Fiction; Contests -- Fiction; End of the world -- Fiction; Great Britain -- History -- Victoria, 1837-1901 -- Juvenile fiction; Great Britain -- History -- Victoria, 1837-1901 -- Fiction; Great Britain -- History -- 19th century -- Fiction; Apocalyptic fiction; Historical fiction; Paranormal fiction